Burnout in nurses - Bogdanovič Gorica; Kulić Veselinka; Kulić Vojo; Živanović Srđan (Association of Nurses Technicians and Midwives, 2018)
Introduction: Burnout syndrome is the answer to chronic, emotional and interpersonal stressors who are related to the workplace. It is characterized by mental or emotional exhaustion, a feeling of fatigue and depression with a more emphasis on psychological than physical symptoms. The aim of this study was to determine the prevalence of burnout syndrome among nurses at the JZU General Hospital Nišić and JZU Health Center Nikšić. Material and methods: The research is designed to the type of section study. The study included 100 nurses at the General Hospital Nikšić and the Health Center Nikšić, different of sex, age, level of education and years of work. The data was collected by the Maslach Burnout Inventory (BMI), consisting of 22 questions posed as a series of claims that are evaluated, using the Likert scale (0-6). Results: Of the total number of respondnents in 36%, there is a burnout syndrome measured by the total MBI score, compared to 64% of subjects with no burnout syndrome. With the help of MBI scale it was found that 8% of respondents have a high level of emotional exhaustion, 38% have a middle level, and the remaining 53% of nurses and technicians have a low level. Conclusion: Based of the results of this research, we can conclude that sex and age of nurses / technicians do not affect the occurrence of a professional burnout syndrome. The nurses / technicians working in primary health care in a significantly lower percentage have a mean level of depersonalization. Also, nurses / technicians with longer length of service show a low level of personal success (achievements).